Population status of the American crocodile, Crocodylus acutus (Reptilia: Crocodilidae) and the caiman, Caiman crocodilus (Reptilia: Alligatoridae), in the Central Caribbean of Costa Rica - Bolaños Montero, Juan Rafael (2019)
Two species of crocodilians have been described in Costa Rica, American crocodile, Crocodylus acutus (Cuvier, 1807), and caiman, Caiman crocodilus (Linnaeus 1758). In Costa Rica, data has been generated on both species, but populations in the Pacific have received more attention from researchers; presumably due to the fact that the Pacific slope has a greater development, which brings greater social pressure on the attention of the incidents generated by the encounter between humans and crocodiles. This study, performed during 2017, was done in an area of approximately 400 km2, characterized by having a wide and dense network of water courses, which includes the Matina, Pacuare, Reventazón and Parismina rivers. In these rivers, an average of 25 kilometers were traveled from the coastline up stream to the interior of the territory, including the Tortuguero canals, and other water bodies that connect these rivers, as well as in the most important lagoons and secondary channels. Three repetitions were made per segment. A population of 1084 caimans and 503 crocodiles is estimated; for a sight count of 8.64 and 2.80 ind/Km respectively. Speaking of caimans, up to 12 % of individuals of reproductive age were observed, while for crocodiles that number was only 2 %. The abundance of both species in the different places studied, turned out to be significantly different for crocodiles and for caimans (Kruskal-Wallis, P ≤ 0.001). Likewise, the size distribution is similar for crocodiles reported in all environments (Kruskal-Wallis, p ≤ 0.15), while for caimans it indicates that there is a different distribution for sizes, according to the environment in which they are found (Kruskal -Wallis, P ≤ 0.001), with a bias against of the Pacuare and Matina rivers. It was possible to estimate a sex ratio of 1.25 and 0.83 males to females, in crocodiles and caimans respectively, with 9 and 11 captures in that same order, in recruit and juvenile sizes.